Effect of plough pans on the growth of soybean roots in the black-soil region of northeastern China - Wen-cai DONG; Qiang FU; Quan-jiu WANG; Cheng-peng CAO (Journal of Integrative Agriculture)
Abstract: Plough pans (PPs), common in the black-soil region of northeastern China, have significant effects on the root systems of crops. We conducted a field experiment to study the distribution of soybean roots under the influence of PPs. The soybean roots showed compensatory growth above the PP, with higher root length and weight in soil with a PP compared to those without a PP. Roots were heavier and longer in the 15–75 cm soil layer without a PP than with a PP. Soil porosity was lower in the PP and the soil below the PP, which likely decreased the oxygen content of the soil and induced more growth of roots above the PP. The PP is also likely to decrease infiltration of rain-water and hinder the migration of nitrate downward, which in turn increased the density and length of soybean root hairs, which, hence, promoted growth.